2002
DOI: 10.1046/j.1365-2834.2002.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of shift patterns on healthcare professionals

Abstract: Aim To compile a literature review of studies on shift work which have relevance to the management of health services personnel. Background In the National Health Service it has always been necessary for certain areas, for example, in-patient services, to provide 24-hour service and hence shift work has been very much a feature of the organization. There is much anecdotal evidence of staff suffering from adverse physical, psychological and social problems that are attributed to the shift patterns they work in.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 31 publications
0
51
0
5
Order By: Relevance
“…It is also recommended in the literature to have a maximum of three consecutive night shifts, few early morning shifts, a limited number of consecutive workdays and quick returns, and to limit weekend work (22,23,30). Implementation of self-rostering did not compromise these recommendations.…”
Section: Garde Et Almentioning
confidence: 99%
“…It is also recommended in the literature to have a maximum of three consecutive night shifts, few early morning shifts, a limited number of consecutive workdays and quick returns, and to limit weekend work (22,23,30). Implementation of self-rostering did not compromise these recommendations.…”
Section: Garde Et Almentioning
confidence: 99%
“…Diminished alertness may be ascribed to the reduction in cardiac sympathetic modulation that occurs when people work at night 3) . In addition, shift workers are known to suffer from relatively higher rates of cardiac, gastrointestinal, and reproductive disorders, which may also be attributable to autonomic imbalance [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have found that chronic insomniacs have an increased risk of coronary artery disease and hypertension (7)(8)(9). Shift workers are prone to higher rates of cardiac, gastrointestinal and reproductive disorders (10,11). Furthermore, shift working nurses have greater difficulty falling or staying asleep; they also frequently suffer from severe autonomic disturbances (6,12).…”
mentioning
confidence: 99%